MAGANG STUDI INDEPENDEN BERSERTIFIKAT WEBSITE APLIKASI ONLINE PMB DI PT ARKATAMA MULTI SOLUSINDO - Syafrizal, Mutiara; Agus Siswanto (Berkah Tematik Mandiri, 2024)
PT Arkatama Multi Solusindo is an experienced company in IT consulting services and application development. Certified Independent Study Database Programming is one of the independent study programs at PT Arkatama Multi Solusindo. The series of activities in the separate database programming study program includes individual learning; participants will take part in a synchronous learning process (delivery of material by the trainer via Zoom meeting) and asynchronous (study of the material provided in the form of teaching modules/teaching videos/practical materials). At each learning meeting, participants will be given a pre-test, post-test, and written or practical assignments to test their understanding of the learning provided by the teacher. The Certified Independent Database Programming Study aims to enable participants to become competent Database Programmers in data management systems. Certified independent study database programming has minimum graduation requirements (SKM), namely, Creating a web-based database application with case studies that have been determined by the trainer to display data in intuitive graphic form and published using a domain and hosting. The final project given was creating a web application for new student admissions using the Codeigniter framework, Bootstrap, and the Highcharts plugin.